Migration, class and environmental inequality: Exposure to pollution in China's Jiangsu Province - Schoolman, Ethan D.; Ma, Chunbo (Ecological economics, 2012)
Systematic research into social inequalities in the distribution of environmental hazards, though well-established in American sociology, has largely not been conducted using quantitative data from developing countries. In this study we consider whether theory and methods developed to test for and explain environmental inequality in the U.S. can be extended to a major developing country such as China. We argue that, due in part to the state's hukou registry system, urban workers in China with an official rural residence may be subject to disproportionate exposure to environmental pollution. We also argue that environmental inequalities in China may be shaped in part by social processes analogous to those which have been held to explain racial differences in pollution exposure in the U.S. In an analysis of the locations and emissions of pollution-producing facilities in China's Jiangsu province, we find that townships with a higher percentage of rural migrants are more likely to be exposed to high levels of air and water pollution. This finding holds even after we control for income and for the presence of “dirty and hard” industries in which rural migrants are most likely to find work. ► We argue that rural migrants in China occupy a place analogous to that of racial minorities in the U.S. ► We examine a major Chinese province for evidence of environmental inequality. ► We consider both facility locations and emissions weighted by proximity to township centers. ► Rural migrants are exposed to disproportionately high levels of pollution. ► This relationship holds after controlling for employment in heavy industries.